Volunteering and Wellbeing Among Ageing Adults: A Longitudinal Analysis - Russell, Allison R.; Nyame-Mensah, Ama; de Wit, Arjen; Handy, Femida (Voluntas (Manchester, England), 2019)
Previous scholarship has shown evidence of a positive relationship between volunteering and improved measures of mental and physical wellbeing. It has also been suggested that volunteering may help individuals navigate transitions between different life stages by encouraging them to become more involved in their communities, thereby building new social connections and improving networks of social support. Using Waves 2 and 3 of panel data from the Midlife in the United States Survey, we examined whether volunteering can buffer against the negative effects of low self-esteem on correlates of psychosocial wellbeing in adults from mid- to later-life. Results indicated that participation in volunteering mitigates the negative effects of adults' low self-esteem on their sense of belonging and life satisfaction. In particular, we determined the adverse effect of negative self-esteem at time T1 on our wellbeing measures (belonging to the community and life satisfaction) at T2 above and beyond the effects of the same measures at T1 and the covariates. Furthermore, we found positive evidence for the moderating influence of volunteering on the relationship between negative self-esteem and both measures of wellbeing, although the effect was stronger for life satisfaction than for belonging. These conclusions suggest that volunteering acts as a buffer for ageing adults, with possible public health implications.